Development of novel auxetic structures based on braided composites - Pichandi, Subramani (2014)
Auxetic materials are a class of materials that expand transversely when stretched longitudinally. Recently, auxetic materials are gaining special interest in the technical sectors mainly due to their attractive mechanical behavior. This paper reports, for the first time, the development of auxetic structures from composite materials and the characterization of their auxetic as well as mechanical properties. Five different auxetic structures were developed varying their structural angle using core reinforced braided composite rods, containing glass fibers for axial reinforcement, polyester filaments for braided structure and epoxy resin as the matrix. Auxetic behavior of these structures was studied in a tensile testing machine using an image-based tracking method. Additionally, an analytical model was used to calculate Poisson’s ratio of these structures. According to experimental and analytical results, auxetic behavior and tensile characteristics of these structures were strongly dependant on their initial geometric configuration (i.e. structural angle). These novel auxetic structures exhibited Poisson’s ratio in the range of 0.30 to 5.20.